Amphibians Animal world (facts and more) - Matrix, Team Book (India Macaw, 2014)
Scientific terminology related to animal world is difficult to understand and often children are less enthusiastic about the subject. So, an entirely attractive series on Animal World has been generated to arouse the interest of children in the subject. The most prominent feature of the series are the colorful pictures, strange facts, simplified content, inclusion of informative end glossary in each book and short sessions of questions and answers.